APRIL Induces a Novel Subset of IgA+ Regulatory B Cells That Suppress Inflammation via Expression of IL-10 and PD-L1 - Fehres, Cynthia M.; van Uden, Nathalie O.; Yeremenko, Nataliya G.; Fernandez, Leticia; Franco Salinas, Gabriela; van Duivenvoorde, Leonie M.; Huard, Bertrand; Morel, Jacques; Spits, Hergen; Hahne, Michael; Baeten, Dominique L. P. (Frontiers in Immunology, 2019)
Regulatory B cells (Bregs) are immunosuppressive cells that modulate immune responses through multiple mechanisms. The signals required for the differentiation and activation of these cells remain still poorly understood. We have already shown that overexpression of A PRoliferation-Inducing Ligand (APRIL) reduces the incidence and severity of collagen-induced arthritis (CIA) in mice. Furthermore, we have described that APRIL, but not BAFF, promoted IL-10 production and regulatory functions in human B cells. Therefore, we hypothesized that APRIL, but not BAFF, may be involved in the induction and/or activation of IL-10 producing Bregs that suppress inflammatory responses in vitro and in vivo. Here, we describe that APRIL promotes the differentiation of naïve human B cells to IL-10-producing IgA+ B cells. These APRIL-induced IgA+ B cells display a Breg phenotype and inhibit T cell and macrophage responses through IL-10 and PD-L1. Moreover, APRIL-induced IL-10 producing Bregs suppress inflammation in vivo in experimental autoimmune encephalitis (EAE) and contact hypersensitivity (CHS) models. Finally, we showed a strong correlation between APRIL and IL-10 in the inflamed synovial tissue of inflammatory arthritis patients. Collectively, these observations indicate the potential relevance of this novel APRIL-induced IgA+ Breg population for immune homeostasis and immunopathology.